Distinguishing Informational Cascades from Herd Behavior in the Laboratory - Çelen, Boğaçhan; Kariv, Shachar (American Economic Review, 2004)
This paper reports an experimental test of how individuals learn from the behavior of others. By using techniques only available in the laboratory, we elicit subjects' beliefs. This allows us to distinguish informational cascades from herd behavior. By adding a setup with continuous signal and discrete action, we enrich the ball-andurn observational learning experiments paradigm of Lisa R. Anderson and Charles Holt (1997). We attempt to understand subjects' behavior by estimating a model that allows for the possibility of errors in earlier decisions.